STRATEGI PENGEMBANGAN AGROINDUSTRI KERIPIK SINGKONG PRIMADONA DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Rukayah, Ira; Khaswarina, Shorea; Edwina, Susy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose ofthis study are: (1) determine the aspects of production, processing aspects, technological,marketingandinstitutionalaspects oftheagroindustryeffortcassava chipsin Pekanbaru(2) developappropriatestrategiesfor thedevelopment ofagroindustryentrepreneursinthe city of Pekanbaru. The research was conductedatSelindungKulim street  km. 15Pembatuandistrict ofTenayanRayaPekanbaru. The method usedis acase studyon the basis thatthe location ofits extensionactivitiesactiveandhave ahighenough income. SWOTanalysisperformedat the gauge. PriorityStrategiesincassava chipsbusiness, namely: (1) increasedservice andproductappearance, (2) standardizingproduct, (3) increase theamountof production, (4) expandingmarket development. Keywords:cassava chips, development, strategy, SWOT